Fangirl [compact disc, unabridged] - Rowell, Rainbow (Listening Library, 2013)
Cath struggles to survive on her own in her first year of college while avoiding a surly roommate, bonding with a handsome classmate who only wants to talk about words, and worrying about her fragile father.